Identification and Validation of Selected Universal Stress Protein Domain Containing Drought-Responsive Genes in Pigeonpea (Cajanus cajan L.) - Sinha, Pallavi; Pazhamala, Lekha T.; Singh, Vikas K.; Saxena, Rachit K.; Krishnamurthy, L.; Azam, Sarwar; Khan, Aamir W.; Varshney, Rajeev K. (Frontiers in Plant Science, 2016)
Pigeonpea is a resilient crop, which is relatively more drought tolerant than many other legume crops. To understand the molecular mechanisms of this unique feature of pigeonpea, 51 genes were selected using the Hidden Markov Models those codes for proteins having close similarity to universal stress protein domain. Validation of these genes was conducted on three pigeonpea genotypes (ICPL 151, ICPL 8755 and ICPL 227) having different levels of drought tolerance. Gene expression analysis using qRT-PCR revealed 6, 8 and 18 genes to be ≥2 fold differentially expressed in ICPL 151, ICPL 8755 and ICPL 227, respectively. A total of 10 differentially expressed genes showed ≥2 fold up-regulation in the more drought tolerant genotype. Of these, four genes each encoded proteins for plant U-box and universal stress protein A- (uspA) like, while one gene encoded for cation/H(+) antiporter protein and one uncharacterized protein. Genes C.cajan_29830 and C.cajan_33874 belonging to uspA, were found significantly expressed in all the three genotypes with ≥2 fold expression variations. Expression profiling of these two genes on the four other legume crops revealed their specific role in pigeonpea. Therefore, these genes seem to be promising candidates for conferring drought tolerance specifically to pigeonpea.